Primary sclerosing cholangitis associated with severe ulcerative colitis in a young man - José Cândido Caldeira Xavier Júnior; Kunie Iabuki Rabello Coelho; Ligia Yukie Sassaki; Fabio da Silva Yamashiro; Kelly Cristhian Lima Oliveira; Maria Aparecida Marchesan Rodrigues (University of São Paulo, 2013)
Primary sclerosing cholangitis, a chronic progressive cholestatic liver disease, is the most serious hepatobiliary complication of ulcerative colitis (UC). The authors present the case of a severe and intractable form of UC associated with primary sclerosing cholangitis, in which the diagnosis of this hepatobiliary complication was made during the postmortem examination. A 19-year-old man, with an 8-month diagnosis of UC, was non-responsive to any therapeutic approach. He presented at the emergency care unit severely ill and with cachexia, and subsequently died of septic shock. The postmortem examination confirmed the clinical diagnosis of severe UC and disclosed the presence of primary sclerosing cholangitis. Although laboratory tests have shown a typical cholestatic profile with elevated alkaline phosphatase and gamma-glutamyl transferase levels, hepatic dysfunction was related to sepsis. This report highlights how challenging the diagnosis of primary sclerosing cholangitis can be and shows the value of the postmortem examination to add important information to a medical diagnosis.